Fueling the Future with Fungi: Efficient Lipid Extraction from Ganoderma Mycelium Biomass - Tangaraju, Merashini; Ilham, Zul; Adlim, Muhammad; Wan-Mohtar , Wan Abd Al Qadr Imad; Jamaludin, Adi Ainurzaman (Progress in Energy and Environment, 2024)
Ganoderma lucidum mycelial biomass produced via submerged-liquid fermentation was subjected to different lipid extraction methods; soxhlet extraction (SXE), solvent extraction (SVE) and ultrasonic-assisted extraction (UAE), followed by a comparison in its lipid yield. The experiment was carried out using 5 g of biomass material, with 50-300 ml hexane solvent, and the temperature was set at 60 ° C for 1-9 hours. It was observed that the lipid yield was found to be influenced by the extraction time and solvent quantity. SVE was observed to be more effective for lipid production of 20.36 % (2 h and 100 ml hexane) in comparison with SXE (18.8 %) and UAE (7.50 %). In general, G. lucidum mycelial biomass may be used as a potential raw material and cost-effective solution for an alternative biodiesel production process in the future. Hence, future research work should focus on other novel extraction techniques as well as optimizing the other extraction parameters in improving the lipid yield from G. lucidum mycelial biomass.